2012
DOI: 10.1371/journal.pone.0038180
|View full text |Cite
|
Sign up to set email alerts
|

Haul-Out Behavior of Harbor Seals (Phoca vitulina) in Hood Canal, Washington

Abstract: The goal of this study was to model haul-out behavior of harbor seals (Phoca vitulina) in the Hood Canal region of Washington State with respect to changes in physiological, environmental, and temporal covariates. Previous research has provided a solid understanding of seal haul-out behavior. Here, we expand on that work using a generalized linear mixed model (GLMM) with temporal autocorrelation and a large dataset. Our dataset included behavioral haul-out records from archival and VHF radio tag deployments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 26 publications
1
49
1
1
Order By: Relevance
“…These results support preliminary surveys in this area which observed that hauled-out seal numbers increased during the ebbing tide, with highest numbers observed from about 3.5 h before low tide until half an hour after (Cunningham et al 2010). So in addition to the in-water behaviour, the haul-out patterns appear relatively unusual and contrasts with the more traditional understanding that haul-out behaviour peaks at the transition of ebb and flood tides (Schneider and Payne 1983; Pauli and Terhune 1987); this adds to increasing evidence that haul-out patterns of harbour seals in some locations may not be driven by tide but by a complex interaction of environmental variables such as diel rhythms (Calambokidis et al 1987; Hamilton et al 2014), predation risk (London et al 2012) and weather conditions (Schneider and Payne 1983; Grellier et al 1996). …”
Section: Discussionmentioning
confidence: 86%
“…These results support preliminary surveys in this area which observed that hauled-out seal numbers increased during the ebbing tide, with highest numbers observed from about 3.5 h before low tide until half an hour after (Cunningham et al 2010). So in addition to the in-water behaviour, the haul-out patterns appear relatively unusual and contrasts with the more traditional understanding that haul-out behaviour peaks at the transition of ebb and flood tides (Schneider and Payne 1983; Pauli and Terhune 1987); this adds to increasing evidence that haul-out patterns of harbour seals in some locations may not be driven by tide but by a complex interaction of environmental variables such as diel rhythms (Calambokidis et al 1987; Hamilton et al 2014), predation risk (London et al 2012) and weather conditions (Schneider and Payne 1983; Grellier et al 1996). …”
Section: Discussionmentioning
confidence: 86%
“…Harbour seals Phoca vitulina have also been observed to avoid contact with humans (Henry & Hammill 2001, London et al 2012, Blundell & Pendleton 2015, and the most critical time for this is thought to be the breeding period. Several studies of pinniped species have indicated that the presence of humans in creases pup mortality (Kenyon 1972, Mattlin 1978, Kovacs & Innes 1990, Stevens & Boness 2003, and there have been suggestions that such disturbance can also affect the breeding success of Saimaa ringed seals (Sipilä 2003, Ministry of the Environment 2011), although the long-term effects on the population are difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Henry and Hammill (2001) suggested that increased leisure activity increased the number of occasions harbour seals were flushed into the water in Métis Bay, Canada. Harbour seals may also switch to a nocturnal haulout pattern to avoid hauling out during the day when daytime anthropogenic activity is high (London, Hoef, Jeffries, Lance, & Boveng, 2012). Harbour seals may also switch to a nocturnal haulout pattern to avoid hauling out during the day when daytime anthropogenic activity is high (London, Hoef, Jeffries, Lance, & Boveng, 2012).…”
Section: Introductionmentioning
confidence: 99%